Labor Induction at 39 Weeks Compared with Expectant Management in Low-Risk Parous Women - Wagner, Stephen M.; Sandoval, Grecio; Grobman, William A.; Bailit, Jennifer L.; Wapner, Ronald J.; Varner, Michael W.; Thorp, John M., Jr.; Prasad, Mona; Tita, Alan T. N.; Saade, George R.; Sorokin, Yoram; Rouse, Dwight J.; Tolosa, Jorge E.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units Network (American Journal of Perinatology, 2020)
Objective Our objective was to compare outcomes among low-risk parous women who underwent elective labor induction at 39 weeks versus expectant management.Study Design This is a secondary analysis of an observational cohort of 115,502 mother–infant dyads who delivered at 25 hospitals between 2008 and 2011. The inclusion criteria for this analysis were low-risk parous women with nonanomalous singletons with at least one prior vaginal delivery after 20 weeks, who delivered at ≥390/7 weeks. Women who electively induced between 390/7 and 396/7 weeks were compared with women who expectantly managed ≥390/7 weeks. The primary outcome for this analysis was cesarean delivery. Secondary outcomes were composites of maternal adverse outcome and neonatal adverse outcome. Multivariable logistic regression was used to estimate adjusted odds ratios (aOR).Results Of 20,822 women who met inclusion criteria, 2,648 (12.7%) were electively induced at 39 weeks. Cesarean delivery was lower among women who underwent elective induction at 39 weeks than those who did not (2.4 vs. 4.6%, adjusted odds ratio [aOR]: 0.70, 95% confidence interval [CI]: 0.53–0.92). The frequency of the composite maternal adverse outcome was significantly lower for the elective induction cohort as well (1.6 vs. 3.1%, aOR: 0.66, 95% CI: 0.47–0.93). The composite neonatal adverse outcome was not significantly different between the two groups (0.3 vs. 0.6%; aOR: 0.60, 95% CI: 0.29–1.23).Conclusion In low-risk parous women, elective induction of labor at 39 weeks was associated with decreased odds of cesarean delivery and maternal morbidity, without an increase in neonatal adverse outcomes.Key Points
Keywords: elective induction; parous pregnancy; cesarean delivery; maternal morbidity